Cytokines and BCR-ABL mediate suppression of TRAIL-induced apoptosis through inhibition of forkhead FOXO3a transcription factor - Ghaffari, Saghi (National Academy of Sciences, 2003)
Cytokine-provided survival signals are known to suppress apoptosis through inhibition of mitochondrial pathways that involve Bcl-2 family members. Here we show that in hematopoietic cells, cytokines also regulate death receptor-mediated pathways. We demonstrate that hematopoietic cytokines such as IL-3 and erythropoietin in normal cells, as well as BCR-ABL oncoprotein in transformed cells, inhibit transcription of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Using small interfering RNAs, we show that the inhibition of TRAIL function is sufficient to partially rescue cytokine-deprived cells from apoptosis. Finally, we demonstrate that cytokine and BCR-ABL suppression of TRAIL transcription is mediated through phosphorylation and inhibition of the forkhead FOXO3a transcription factor. BCR-ABL-induced inhibition of TRAIL transcription in hematopoietic cells may provide a novel mechanism for tumorigenicity in chronic myeloid leukemia.